Belgian agriculture and rural environments - Etienne Van Hecke; Henk Meert; Charles Christians (Belgeo)
Over recent years, the rural world has changed from being mono-functional to being multi-functional, partly as a result of the evolution of modern society, which now demands areas for activities such as tourism, recreation and rural housing. Agriculture often plays a minor role in such profound transformations. It is faced with stronger rules to protect nature and with tough competition for the use of rural space. Those working in agriculture are confronted with low incomes and find it increasingly difficult to catch up with the income earned in other sectors. The first and the second section of this article therefore deal with such present-day economic and environmental problems that are related to Belgian agriculture and the remaining rural environments. These problems are discussed and differentiated according to the regions that are taken into account. A third section assesses the answer of the Common Agriculture Policy to these problems.